L’Association des États de la Caraïbe et la planification spatiale marine - Michel Desse; Romain Legé (Études Caribéennes)
The Association of Caribbean States is an archipelagic territory where the sea is considered as a common heritage. Caribbean states have seen an increase of activities and uses at sea, particularly related to tourism, shipping and fishing. This is why measures to protect the coastal and marine environment have been decided, like Marine protected areas. Recently, some States wanted to become part of a broader international movement of marine spatial planning. This article proposes to analyse the objectives and progress of the implementation of Marine Spatial Planning in the Caribbean.